When secretion turns into excretion – the different roles of IgA - Strugnell, Richard A. (Frontiers in Immunology, 2022)
IgA deficiency is the commonest immunodeficiency affecting up to 1 in 700 individuals. The effects of IgA deficiency are difficult to see in many individuals, are mild in many fewer and severe in fewer still. While monovalent IgA is found in serum, dimeric IgA is secreted through mucosal surfaces where it helps to maintain epithelial homeostasis. Studies with knockout mice have taught us that there are subtle inflammatory consequences of removing secretory IgA (sIgA), and the best explanation for these changes can be related by the loss of the ‘excretory’ immune system. The excretion of antigens is a logical process in regulating the immune system, given the long half life of complement fixing antibodies. But the function of IgA as an immune or inflammation regulator may go beyond antigen removal.